Reliability and validity of the Carminatti's test for aerobic fitness in youth soccer players - Teixeira, A. S.; da Silva, J. F.; Carminatti, L. J.; Dittrich, N.; Castagna, C.; Guglielmo, L. G. A. (The Journal of Strength and Conditioning Research, 2014)
In this study, we examined the reliability and validity of peak velocity determined using the Carminatti's test (PVT-CAR) to evaluate the aerobic fitness of young soccer players (age = 13.4 ± 1.2 years; range, 10.3-15.4 years). To determine test-retest reliability of PVT-CAR, 34 adolescents (U-12, n = 13; U-14, n = 21) performed the Carminatti's test twice within 3-5 days. Validity was assessed in 43 adolescents (U-14, n = 20; U-16, n = 23) submitted to both the Carminatti's test and an incremental treadmill test to determine their aerobic fitness indicators. The intraclass correlation of PVT-CAR was 0.89, 0.93, and 0.81 with a coefficient of variation of 2.30% (0.33 km/h), 1.89% (0.26 km/h), and 2.66% (0.39 km/h) for the total sample (pooled data) or separately for the U-12 and U-14 groups, respectively. No significant difference was found between PVT-CAR and maximal aerobic speed (MAS) for the total sample (pooled data) or separately for the U-14 and U-16 groups. In addition, Bland and Altman plots evidenced acceptable agreement between them. The PVT-CAR was significantly related with peak velocity and MAS obtained in the incremental test for the total sample (r = 0.86 and 0.81, p < 0.01, respectively) and separately for the U-14 (r = 0.84 and 0.75, p < 0.01, respectively) and U-16 groups (r = 0.60 and 0.58, p < 0.01, respectively). Furthermore, the PVT-CAR was correlated with the VO2peak (r = 0.57, p < 0.01) and the velocity associated to the second ventilatory threshold (r = 0.69, p < 0.01) when the data were pooled (total sample). As a result, the Carminatti's test may be considered as a reliable and valid measure for assessing and monitoring the development of MAS of young soccer players during adolescence.